2017
DOI: 10.29333/ejgm/81889
|View full text |Cite
|
Sign up to set email alerts
|

A case report of primary tuberculosis of the tongue

Abstract: At present, the rate of extrapulmonary tuberculosis is gradually increasing among all tuberculosis cases. The secondary tuberculosis of oral cavity represents 0.2-1.5% of all cases with extrapulmonary tuberculosis. Although incidence of oral lesions secondary to pulmonary tuberculosis ranges from 0.4% to 1.5%, primary tuberculosis of the tongue occurs very rare, and it is published only as isolated case reports. A male patient presented to our dermatology clinic with complaints of painful ulcerated white plaqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…Moreover, Nokhostin and Zafarmand (2016) conducted a study on 600 Iranian dentists and reported neck (51.87%), wrist and hand (29.62%), back (11.11%), Figure 1: Distribution of dentists based on intensity of musculoskeletal disorders before and after intervention considering the involved body area and shoulder (7.40%) as the most involved parts of body [11]. The study carried out by Rahnamaye Tamrooiy et al (2015) examined 98 dentists in Tehran and reported the highest prevalence of musculoskeletal disorders in neck (78.3%), shoulder (76.4%), wrist (68.5%), and lower back (55.4%) [17]. Sharma and Golcha (2010) conducted a study on 102 dentists and reported the highest prevalence of work-related musculoskeletal disorders in lower back, neck and shoulder within recent 6 months [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Nokhostin and Zafarmand (2016) conducted a study on 600 Iranian dentists and reported neck (51.87%), wrist and hand (29.62%), back (11.11%), Figure 1: Distribution of dentists based on intensity of musculoskeletal disorders before and after intervention considering the involved body area and shoulder (7.40%) as the most involved parts of body [11]. The study carried out by Rahnamaye Tamrooiy et al (2015) examined 98 dentists in Tehran and reported the highest prevalence of musculoskeletal disorders in neck (78.3%), shoulder (76.4%), wrist (68.5%), and lower back (55.4%) [17]. Sharma and Golcha (2010) conducted a study on 102 dentists and reported the highest prevalence of work-related musculoskeletal disorders in lower back, neck and shoulder within recent 6 months [16].…”
Section: Discussionmentioning
confidence: 99%
“…According to statistical analysis, there was a significant relation between gender, height, weight, number of patients per day, obesity, marital status, and prevalence of musculoskeletal disorders (P>0.05) while there was not any significant relation between work hours per week, work experience, training experience in field of ergonomics and prevalence of musculoskeletal disorders (P<0.05). Findings showed the suitable interventions such as re-design of work place and instruments, creation of basic information about proper posture, and introducing the role of body posture and biomechanics in prevalence of musculoskeletal disorders to dentists and passing ergonomics by dentistry students are essential actions regarding reduction in musculoskeletal disorders and increase in dentists' productivity [17]. Dentists are at risk of more occupational musculoskeletal disorders due to their job and services.…”
Section: Introductionmentioning
confidence: 99%
“…Туберкулезный глоссит -очень редкое явление даже в странах с высоким бременем туберкулеза. Язык является наиболее частым очагом поражения в структуре оральных форм, частота которого не превышает 0,1% [20,21]. По мнению ученых, наиболее вероятный путь внедрения МБТ в слизистую оболочку языка -спутогенный (с мокротой) при массивном бактериовыделении из верхних дыхательных путей или гематогенный из других первичных очагов [22].…”
unclassified